Duration of biodynamic changes associated with water resistance therapy. (3rd July 2021) - Echternach, Matthias; Köberlein, Marie; Gellrich, Donata; Guzman, Marco; Laukkanen, Anne Maria; Burk, Fabian; Döllinger, Michael; Richter, Bernhard; Kainz, Marie-Anne
Abstract: Introduction: In current voice research, there is a growing interest in semi-occluded vocal tract exercises and their contribution to an increased vocal efficiency. However, there are only few studies on the lasting effects. Material and methods: Eight vocally healthy subjects were asked to sustain a phonation at a comfortable loudness on the vowel /i/, with a Fundamental Frequency of 250 Hz (females) or 125 Hz (males). During phonation the subjects were simultaneously recorded with transnasal High Speed Videoendoscopy (HSV, 20, 000fps), electroglottography, and audio signals. The subjects then performed a water resistance therapy (WRT) for 10 min (tube: 30 cm length, 5 cm below water surface, diameter 9 mm). Repeated measurements of sustained phonation were performed 0, 5, 10, 20, and 30 min after exercising. From the HSV material the Glottal Area Waveform (GAW) was segmented and GAW parameters were computed. Results: There were strong inter-individual differences concerning the changes of different measures over time after WRT. In general, directly after WRT there was a lowering of the GAW derived Period Perturbation Quotient, a lowering of the Closing Quotient and an increase of the Sound Pressure Level (SPL) in comparison to the pre-intervention measurement. However, only 5 min post WRT there was no longer a clear difference compared to baseline results before WRT. Other values such as Open Quotients exhibited no evident changes by WRT at any timepoint. Conclusions: WRT showed strong inter-individual effects concerning the changes in the evaluated measures post-intervention. General tendencies of some measures directly after the intervention showed a brief effect of only a few minutes.